Environmental Health Risks After the 2023 Turkey-Syria Earthquake and Salient Mitigating Strategies: A Critical Appraisal - Sirwan Khalid Ahmed; Deepak Chandran; Safin Hussein; Praveen SV; Sandip Chakraborty; Md. Rabiul Islam; Kuldeep Dhama (SAGE Publishing, 2023)
A 7.8-magnitude earthquake in Turkey and Syria, followed by a 7.6-magnitude earthquake, caused over 50 000 deaths and over 100 000 injuries. The immediate physical injuries were severe, but the health repercussions, including the strain on healthcare services and the possibility of disease outbreaks, were equally concerning. Infections due to multidrug resistant microbes were also a matter of concern. Earthquake has caused not only loss of property and physical damage but also has a great negative impact on the mental health of the people. It is associated with serious psychological trauma. Moreover, the risk of malnutrition also became evident. Food aid and nutritional supplements can reduce the risk of malnutrition, but they are not a long-term solution. Establishment of sustainable food systems and restoration of agricultural productions are essential. Other demanding issues like derth of access to essential services related to health care, chances of child birth related complications following earthquake also need to be addressed. Emerging crises and disasters (conflicts, pandemics, epidemics), in addition to pre-existing conditions (collapsed health facilities, cold winter conditions, destruction of lifeline infrastructures, overcrowding in emergency shelters, poor sanitation, and unfavorable socio-economic conditions), may further exacerbate the already precarious public health situation and significantly delay the recovery process. The early warning and protection against the development of infectious diseases in earthquake-affected areas depend on good disease surveillance at the local and regional levels, which has been proposed as one of several techniques for prevention and management of infectious diseases in these areas. Our article outlines high-level approaches to reduce the risk of health issues among victims of Turkey and Syria.